To solve this system of equations, we can use the substitution method.
First, we will solve the first equation for x:
-x + 6y = 13
x = 6y + 13
Now, we will substitute x into the second equation:
4(6y + 13) - 10y = -10
24y + 52 - 10y = -10
14y + 52 = -10
14y = -62
y = -62/14
y = -31/7
Now that we have found the value of y, we can substitute it back into the first equation to find x:
x = 6(-31/7) + 13
x = -186/7 + 13
x = -186/7 + 91/7
x = -95/7
Therefore, the solution to the system of equations is:
x = -95/7
y = -31/7
–x+6y=13
4x–10y=–10
1 answer